Validation of remote mapping of cochlear implants. (June 2014) - Eikelboom, Robert H; Jayakody, Dona MP; Swanepoel, De Wet; Chang, Samuel; Atlas, Marcus D
Recipients of cochlear implants need to attend regular mapping sessions to adjust their speech processors. We developed a PC-based system for remote mapping, which employed voice, video and text communication. Eleven implant recipients had their implant electrodes programmed (mapped) both by conventional methods and remotely. Speech tests, conducted by a family member or research assistant, were used to test the outcome of the programming during the remote consultation. The recipient and audiologist were surveyed regarding aspects of the teleconsultation. There were no significant differences between conventionally and remotely programmed electrode settings. The speech test results were perfect in most cases. The average time to complete the conventional mapping session was 37 min and the average time for the remote mapping session was 42 min ( P = 0.034). Recipients and the audiologist reported favourably on most aspects of the consultations. Lack of synchronisation between voice and video was the most common problem, which disrupted communication. The assistant was important to overcome this problem. All but one participant indicated they would be willing to use tele-mapping in the future. Remote programming of cochlear implants can be conducted reliably with relatively simple equipment, potentially in the homes of remotely located patients assisted by a family member.